Profile of Students Communication Skills on Global Warming and Pollution Subject Using Conference Assessment - T. Gustiani; W. Ana Ratna; R. Solihat (Universitas Sebelas Maret, 2017)
This research purpose is to analyze the student’s communication skills using the conference assessment and student response of conference assessment implementation on global warming and pollution subject. The method used is descriptive. Participants included 34 students 11th grade in senior high school. Conference assessment applied through project based learning on global warming and pollution subject. Conference assessment consists of written conference using online access and oral conference in face-to-face classrooms. The conference was held in three sessions (project planning, project work, and project reflection). Students communication skills consist of five indicators based on 21st skills. The indicator was 1) articulate thoughts and ideas effectively; 2) listen effectively; 3) use communication for a range of purposes; 4) utilize multiple media and technologies; and 5) communicate effectively in diverse environments. The average score of communication skill skills categorized into three groups: high, medium and low. The data showed that three indicators in high categorized (83.09% in the second indicator during oral conference, 77.94% in the fourth indicator and 88.97% in the fifth indicator). And three indicators in medium categorized (64,71% in the first indicator, 56.62% in second indicator during written conference and 69.85% in the third indicator). Students showed a positive response to the implementation and results of conference assessment.